Highly graphitized carbon from non-graphitizable raw material and its formation mechanism based on domain theory. (September 2017) - Kim, Doo-Won; Kil, Hyun-Sig; Kim, Jandee; Mochida, Isao; Nakabayashi, Koji; Rhee, Choong Kyun; Miyawaki, Jin; Yoon, Seong-Ho
Abstract: This work demonstrates conversion of non-graphitizable carbon (NGC) to graphitizable carbon (GC) by NaOH treatment of carbonized spherical phenol resin (SPR). The degree of graphitization of the studied SPRs was confirmed using X-ray diffraction and Raman spectroscopy, and their morphologies were observed with scanning electron microscopy and scanning tunneling microscopy. Graphitization of amorphous carbonized SPR at 2800 °C was performed; however, the degree of graphitization was low to indicate that carbonized SPR was non-graphitizable. NaOH treatment of carbonized SPR endowed fairly high degree of graphitization; graphitization of carbonized SPR following NaOH activation improved the degree of graphitization. Thus NaOH treatment was demonstrated to convert non-graphitizable SPR to graphitizable one. The role of NaOH was suggested in terms of hierarchical domain structure model. NaOH treatment could successfully destroy micro-domains of carbonized SPR via sodium intercalation/deintercalation and catalytic gasification with deintercalated sodium atoms with releasing hydrogen and gaseous carbon oxides and decreasing alkyl groups, and reconstruct the new larger clusters and micro-domains merged together to relieve the distortion stresses. Thus merged micro-domains would be critical in the conversion of NGC to GC. The presented findings open up a possibility to control the properties of carbon materials by manipulation of their domain structures. Graphical abstract: